Nyadran Tradition Procession: A Cultural Study at the Tomb of Sheikh Maulana Abdurrahman in Demak - Alfaris, Muhrafi (Journal of Noesantara Islamic Studies, 2025)
The purpose of the author’s research is to find out the relationship between Sheikh Maulana Abdurrahman Al-Bar and the villagers of Betahwalang, Wedung Subdistrict and Gempolsongo, Mijen Subdistrict, where when the rice harvest season is over they are always crowded (hundreds of attendees) attending the Nyadran Tradition event in Mutih Kulon Village by renting public transportation (Bus), and describing the procession of the Nyadran Tradition event at Burwatu Cemetery. The research method is descriptive qualitative with observation, literature study, and interviews. The results of the author’s research that both villagers (Betahwalang and Gempolsongo) believe that the existence of this village originated from the figure of Sheikh Maulana Abdurrahman Al-Bar who cleared the forest in ancient times, then they are now crowded to attend the event regularly once a year. The conclusions of this research are: first, the existence of the Nyadran Tradition at Burwatu Tomb originated from the concerns of religious figures who saw the people of Mutih Kulon Village who visited the tomb in seclusion. Second, the relationship between the figure of Sheikh Maulana Abdurrahman Al-Bar and the villagers of Betahwalang and Gempolsongo is only limited to emotional/mahabbah relationships. Third, the procession of Nyadran Tradition events at Burwatu Tomb is in the form of Fatayatan, Sholawat Nariyah, Burdahan, Khotmil Qur’an, Istigotsah, and Nyadran Akbar.